Analisis Tingkat Kepuasan Mahasiswa Universitas Palangkaraya Terhadap Layanan Sistem Informasi SIUBER Menggunakan Metode End-User Computing Satisfaction (EUCS) - Parhusip, Jadiaman; Sanusie, Arbiyanoor Ilham; Sambelorang, Yosua; Imanuel, Rangga (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The SIUBER Information System is a strategic instrument supporting academic efficiency at Universitas Palangkaraya. However, system implementation requires continuous evaluation to ensure it meets end-user expectations. This study aims to evaluate student satisfaction with SIUBER services using the End-User Computing Satisfaction (EUCS) method developed by Doll and Torkzadeh. The assessment encompasses five core dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. This research was conducted as a pilot study involving 20 active users as respondents. Reliability testing confirmed the instrument's high consistency with a Cronbach's Alpha of 0.917. The findings revealed that the Format dimension achieved the highest satisfaction score (3.82), indicating a highly intuitive user interface. Conversely, the Timeliness dimension received the lowest score (2.71), specifically regarding system stability issues. This evaluation highlights that while the system's usability is excellent, urgent improvements in server infrastructure are required to enhance system stability and maintain user trust.